Students' Mathematical Representation in Solving Exponential Function - Nurul Audhifa Utami; Cholis Sa'dijah; Tjang Daniel Chandra (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
One of the important abilities that students need to master when learning mathematics is mathematical representation. This ability will improve students' understanding of concepts, principles and procedures in solving mathematical problems. But in reality, many students have difficulty in conveying their ideas to solve mathematical problems and this has an impact on students' mathematical representation. This research aims to describe the low mathematical representation of students and the factors that caused this. The type of research used is descriptive research with a qualitative approach. Based on this research, it is known that 66.67% of class X MIPA VII students at SMA Negeri 1 Ampek Angkek have low mathematical representation in solving exponential function problems. These results show that students' representation is still low due to difficulty writing down question solving ideas to the use of incorrect settlement intuition. Salah satu kemampuan penting yang perlu dikuasai siswa saat pembelajaran matematika adalah representasi matematis. Kemampuan ini akan meningkatkan pemahaman siswa tentang konsep, prinsip dan prosedur dalam menyelesaikan masalah matematis. Namun kenyataannya, banyak siswa mengalami kesulitan dalam menyampaikan ide-idenya untuk menyelesaikan masalah matematika dan hal tersebut berdampak pada representasi matematis siswa. Penelitian ini bertujuan untuk mendeskripsikan representasi matematis siswa yang rendah serta faktor yang menyebabkan hal tersebut terjadi. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Berdasarkan penelitian ini, diketahui bahwa sebanyak 66,67% siswa kelas X MIPA VII di SMA Negeri 1 Ampek Angkek memiliki representasi matematis yang rendah dalam menyelesaikan masalah fungsi eksponensial. Hasil ini menunjukkan bahwa representasi siswa yang masih rendah yang diakibatkan oleh kesulitan menuliskan ide penyelesaian soal hingga penggunaan intuisi penyelesaian yang salah.